2013
DOI: 10.4314/thrb.v15i2.3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Chlamydia trachomatis infection among infertile males and its association with abnormal semen characteristics in Delta State, Nigeria

Abstract: Chlamydia trachomatis is the most common cause of sexually transmitted diseases that is not of viral origin and there is accumulating evidence of a significant role played by this pathogen in causing male factor infertility. This study thus aimed to determine the prevalence of C. trachomatis among infertile males and to evaluate their association with fertility status and abnormal semen characteristics. This study included 215 infertile male subjects who visited a major fertility clinic in Warri, Delta state, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In Osazuwa et al 23 , a significantly higher prevalence of C. trachomatis antibodies was observed in men aged 20-29 and 30-39 years. Abayomi et al 58 attempted to establish a synergistic relationship between age and BMI in sperm parameters to document alterations in volume, liquefaction time, motility, and sperm count at age less than 45 years and at age 45 years and above.…”
Section: Socio-demographic Risk Factorsmentioning
confidence: 86%
See 1 more Smart Citation
“…In Osazuwa et al 23 , a significantly higher prevalence of C. trachomatis antibodies was observed in men aged 20-29 and 30-39 years. Abayomi et al 58 attempted to establish a synergistic relationship between age and BMI in sperm parameters to document alterations in volume, liquefaction time, motility, and sperm count at age less than 45 years and at age 45 years and above.…”
Section: Socio-demographic Risk Factorsmentioning
confidence: 86%
“…The study also showed that previous penile discharge, painful micturition, and previous genital ulcer were associated with infertility in men. 22 Similarly, Osazuwa et al 23 reported a higher prevalence of Chlamydia trachomatis antibodies among infertile men and its relationship with abnormal semen features. C. trachomatis antibodies were identified in 19.5% of the 215 infertile males in the study.…”
mentioning
confidence: 97%
“…Some epidemiological studies have shown that CT infection is significantly correlated with azoospermia and oligozoospermia, 21 22 while other reports have shown that CT infection is not associated with decreased semen quality or male infertility. 23 24 …”
Section: Discussionmentioning
confidence: 98%
“…In Nigeria, studies have shown the prevalence of C. trachomatis ranged from 19.5% to 91.2% across different populations including patients attending gynaecological clinics (Jatau et al, 2009;Ebhohimhen et al, 2010;Osazuwa et al, 2013;Okoror et al, 2014). Ethiope West, Sapele, Warri North and South have a population of 203592, 142652, 137300 and 303417 respectively (Population Census, 2006).…”
Section: Introductionmentioning
confidence: 99%